Synthesis and characterization of degradation impurities of Flucloxacillin and Dicloxacillin. (30th January 2023) - Pindi, Santhosh Reddy; Reddy, Aaramadaka Sunil Kumar; Gollapalli, Venkateswara Rao; Sanasi, Paul Douglas; Nandi, Sukumar; Velugula, Siva Rama Kasibabu; Chavakula, Ramadas
Abstract: A series of degradation impurities of Flucloxacillin and Dicloxacillin were synthesized. The formation and a facile synthesis of each impurity were presented in detail, namely penicilloic acids of Dicloxacillin (3) (Ph.Eur. Impurity‐A), Dicloxacillin glycine analog (4), Dicloxacillin penilloic acids (5) (Ph.Eur. Impurity‐B), Dicloxacillin Pencillamide (6), N‐Acetylated penicilloic acid of Dicloxacillin (7), DCMICAA adduct of Dicloxacillin penicilloic acid (8), Flucloxacillin glycine analog (Ph.Eur. Impurity‐F) (9), penicilloic acids of Flucloxacillin (10), penilloic acids of Flucloxacillin (11), CFMICAA adduct of Flucloxacillin penicilloic acid (Flucloxacillin Ph.Eur. Impurity‐H) (12), Flucloxacillin Penicillamide (Flucloxacillin Ph.Eur. Impurity‐E) (13), and N‐Acetylated penicilloic acid of Flucloxacillin (14). These impurities are extensively characterized by various analytical techniques. Abstract : Degrdation impurities of Flucloxacillin & Dicloxacillin.